Analysis of Usage of Electronic Resources by the Department of Science and Technology (DST) Institutions in India - Adhikari, Saumen (Journal of Information and Knowledge, 2017)
In the digital era, research scientists are predominantly dependent on electronic resources (e-resources) to fulfill their information needs. Consortia have facilitated access to numerous electronic information resources in S&T institutions. The DST, Government of India supports 20 autonomous R&D institutions that have access to information resources through a consortium. This paper studies the electronic resource use pattern by DST institutes. Institutional downloads are given and the leading publishers relevant to the institutions are listed. Finally, for better utilization of e-resources, an information filtration model has been proposed.